Differential Change in Hippocampal Radial Astrocytes and Neurogenesis in Shorebirds With Contrasting Migratory Routes - Mendes de Lima, Camila; Douglas Corrêa Pereira, Patrick; Pereira Henrique, Ediely; Augusto de Oliveira, Marcus; Carvalho Paulo, Dario; Silva de Siqueira, Lucas; Guerreiro Diniz, Daniel; Almeida Miranda, Diego; André Damasceno de Melo, Mauro; Gyzely de Morais Magalhães, Nara; Francis Sherry, David; Wanderley Picanço Diniz, Cristovam; et al. (Frontiers in Neuroanatomy, 2019)
Little is known about environmental influences on radial glia-like (RGL) α cells (radial astrocytes) and their relation to neurogenesis. Because radial glia is involved in adult neurogenesis and astrogenesis, we investigated this association in two migratory shorebird species that complete their autumnal migration using contrasting strategies. Before their flights to South America, the birds stop over at the Bay of Fundy in Canada. From there, the semipalmated sandpiper (Calidris pusilla) crosses the Atlantic Ocean in a non-stop 5-day flight, whereas the semipalmated plover (Charadrius semipalmatus) flies primarily overland with stopovers for rest and feeding. From the hierarchical cluster analysis of multimodal morphometric features, followed by the discriminant analysis, the radial astrocytes were classified into two main morphotypes, Type I and Type II. After migration, we detected differential changes in the morphology of these cells that were more intense in Type I than in Type II in both species. We also compared the number of doublecortin (DCX)-immunolabeled neurons with morphometric features of radial glial–like α cells in the hippocampal V region between C. pusilla and C. semipalmatus before and after autumn migration. Compared to migrating birds, the convex hull surface area of radial astrocytes increased significantly in wintering individuals in both C. semipalmatus and C. pusilla. Although to a different extent we found a strong correlation between the increase in the convex hull surface area and the increase in the total number of DCX immunostained neurons in both species. Despite phylogenetic differences, it is of interest to note that the increased morphological complexity of radial astrocytes in C. semipalmatus coincides with the fact that during the migratory process over the continent, the visuospatial environment changes more intensely than that associated with migration over Atlantic. The migratory flight of the semipalmated plover, with stopovers for feeding and rest, vs. the non-stop flight of the semipalmated sandpiper may differentially affect radial astrocyte morphology and neurogenesis.